OPTIMIZING PREFABRICATED BUILDING INDUSTRY INTEGRATION: A STUDY OF CONSTRUCTION THROUGH INDUSTRIAL SUPPLY CHAIN DYNAMICS AND UPSTREAM/DOWNSTREAM ENTERPRISE ACCESS STANDARDS - Ahmad Wisal; Shasha Xie (Spectrum of Engineering Sciences, 2025)
This study examines the supply chain integration in the prefabricated building industry, focusing on the relationship between upstream and downstream enterprises. The research identifies critical risk factors across the project lifecycle using an Importance-Performance Analysis. Key findings reveal that major risks like high costs and policy changes, are more prevalent in the early project stages, while risk management is weakest in later stages, particularly in manufacturing and construction. The study highlights challenges in standardization, quality control, and technology adoption, emphasizing the importance of government policies and industry standards in shaping supply chain integration. Strategies for enhancing integration are proposed, including the development of industry-wide standards, investment in skills training, and adopting a lifecycle approach to project management.